2004
DOI: 10.1097/00005537-200403000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Does Cerumen Have a Risk for Transmission of Hepatitis B?

Abstract: Cerumen can be a potential source of transmission. Therefore, this route should be investigated in further studies for horizontal, nosocomial, and occupational transmission of hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…5 Kalcioglu et al examined 40 patients with HBV (indicated by positive serum samples); HBV DNA was found in 11 of the 40 cerumen specimens (27.5 per cent). 12 In our study, HBV DNA was detected in the cerumen samples of 2 out of 30 patients (6.6 per cent). Hence, the results of this study and those of previous studies indicate that cerumen can be a potential source of transmission of HBV.…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…5 Kalcioglu et al examined 40 patients with HBV (indicated by positive serum samples); HBV DNA was found in 11 of the 40 cerumen specimens (27.5 per cent). 12 In our study, HBV DNA was detected in the cerumen samples of 2 out of 30 patients (6.6 per cent). Hence, the results of this study and those of previous studies indicate that cerumen can be a potential source of transmission of HBV.…”
Section: Resultssupporting
confidence: 43%
“…Hence, the results of this study and those of previous studies indicate that cerumen can be a potential source of transmission of HBV. 5,12 Variations in the results of these studies (i.e. the lower percentage of HBV DNA in cerumen samples in the present study) may be due to the different methods of sampling used.…”
Section: Resultsmentioning
confidence: 68%
“…In addition, the study also showed positive correlation between serum HBV DNA levels and the positivity of HBV DNA in cerumen (3). Several authors have suggested that cerumen can be a potential source for the transmission of HBV and human immunodeficiency virus (3,4).…”
supporting
confidence: 56%
“…Several studies showed some relationship between HBV DNA levels of serum and other body fluids, indicating that HBV DNA levels were higher in the serum compared with other body fluids. However, when HBV DNA levels are high in the serum, it is very likely to be detected in body fluids such as cerumen, saliva, and semen (3,10). In the present study, HBV DNA was detected in 66.7% of the cerumen and 100% of the otorrhea by using quantitative polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 44%
“…There was close correlation between serum HBV DNA levels and cerumen HBV DNA positivity. 5 These results made us suspicious about a similar risk for HCV transmission, and we investigated quantitative HCV-RNA in cerumen of the chronically HCV-infected patients by polymerase chain reaction (PCR) to clarify the risk of transmission.…”
Section: Introductionmentioning
confidence: 99%